2013
DOI: 10.1152/ajplung.00162.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sustained inflation at birth did not protect preterm fetal sheep from lung injury

Abstract: Hillman NH, Kemp MW, Noble PB, Kallapur SG, Jobe AH. Sustained inflation at birth did not protect preterm fetal sheep from lung injury. Am J Physiol Lung Cell Mol Physiol 305: L446 -L453, 2013. First published July 19, 2013 doi:10.1152/ajplung.00162.2013.-Sustained lung inflations (SI) at birth may recruit functional residual capacity (FRC). Clinically, SI increase oxygenation and decrease need for intubation in preterm infants. We tested whether a SI to recruit FRC would decrease lung injury from subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
81
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 41 publications
6
81
2
Order By: Relevance
“…This was intentional to allow isolation of the inflammatory events occurring in early life from those of the injurious cycle of ongoing mechanical ventilation, but the relatively short study duration, although still longer than many previous SI animal studies (26,29,32,33,36), was unlikely to be sufficient to result in posttranscription protein changes within the lung and correlation with the histology findings. We chose accepted markers of preterm lung injury known to be upregulated within 30 min of injurious ventilation (11,12,14,40), but clear patterns for specific mechanisms of injury were not apparent. This may have been influenced by the sample size of each treatment group and the large variability in mRNA expression due to the multiple influences beyond those variables controlled in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was intentional to allow isolation of the inflammatory events occurring in early life from those of the injurious cycle of ongoing mechanical ventilation, but the relatively short study duration, although still longer than many previous SI animal studies (26,29,32,33,36), was unlikely to be sufficient to result in posttranscription protein changes within the lung and correlation with the histology findings. We chose accepted markers of preterm lung injury known to be upregulated within 30 min of injurious ventilation (11,12,14,40), but clear patterns for specific mechanisms of injury were not apparent. This may have been influenced by the sample size of each treatment group and the large variability in mRNA expression due to the multiple influences beyond those variables controlled in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested SI improved aeration, FRC, and cerebral oxygen delivery (29,32,33), while others failed to demonstrate any benefit over standard respiratory support with sufficient PEEP (26,(35)(36)(37). SI was associated with increased lung injury in two studies (11,12). These data suggest the optimal SI strategy still needs to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study using intubated preterm lambs, we systematically describe the interrelationship between the use of antenatal corticosteroids, exogenous surfactant therapy, and two distinct recruitment strategies applied Unlike previous animal studies of respiratory care at birth (6,(10)(11)(12)15,16,(20)(21)(22)(27)(28)(29)(30), our study involved a large sample size. Pooling all epochs, the use of an OLV stepwise PEEP approach significantly improved C dyn and oxygenation compared to a 30-s 40 cmH 2 O SI.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely examined intentional recruitment maneuver at birth is the use of an initial sustained inflation (SI) to clear fetal lung liquid from the airways (18,19). Preclinical experimental studies of SI have been mixed (5,6,(9)(10)(11)20), with an increase in lung injury reported in some studies (21)(22)(23). Improved short-term respiratory outcomes have been reported in some clinical trials (24,25), although without long-term benefits, and an increased risk of patent ductus arteriosus (19).…”
mentioning
confidence: 99%